The Anatolian Journal of Cardiology 2021
DOI: 10.5152/anatoljcardiol.2021.36214
|View full text |Cite
|
Sign up to set email alerts
|

Common single nucleotide polymorphisms in the FNDC5 gene and serum irisin levels in acute myocardial infarction

Abstract: Objective: Acute myocardial infarction (AMI) is the most common type of coronary artery disease. The irisin hormone encoded by the fibronectin type III domain-containing protein-5 (FNDC5) gene is synthesized in muscle, heart, and fat tissues. The present study aims to investigate serum irisin concentrations and FNDC5 genetic variants in patients with AMI through comparison with controls. Methods: This study included 225 patients with AMI and 225 healthy subjects. Blood samples were obtained from patients durin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 36 publications
0
3
0
Order By: Relevance
“…To complement the assessment of irisin at the protein level, we also assessed whether the observed differences resulted from genetic variability. Although previous research has reported contradictory findings on this association [29], irisin polymorphisms have been associated with obesity and related comorbidities [30]. The rs3480 noncoding polymorphism of FNDC5 is of interest here, given its association with blood pressure and lipid profiles [31].…”
Section: Discussionmentioning
confidence: 93%
“…To complement the assessment of irisin at the protein level, we also assessed whether the observed differences resulted from genetic variability. Although previous research has reported contradictory findings on this association [29], irisin polymorphisms have been associated with obesity and related comorbidities [30]. The rs3480 noncoding polymorphism of FNDC5 is of interest here, given its association with blood pressure and lipid profiles [31].…”
Section: Discussionmentioning
confidence: 93%
“…Fourth, the combination of radiomics characteristics and genomic data is described as radiogenomics (11). Gene regulation plays an important role in the occurrence of MI and cardiac remodeling after MI (72,73). In the future, combinations of TA features and genomic data may have potential clinical application value in MI.…”
Section: Prospectsmentioning
confidence: 99%
“… 7 Irisin is encoded by the fibronectin type III domain containing protein 5 ( FNDC 5) gene. 8 , 9 As a precursor of irisin, FNDC5 is highly expressed in the heart, brain, liver and skeletal muscle, and is essential for maintaining metabolic homeostasis. 10 , 11 It has been reported that the levels of FNDC5 mRNA in adipose tissue and circulating irisin negatively correlated with hyperglycaemia, triglycerides, visceral adiposity and extramyocellular lipid deposition.…”
Section: Introductionmentioning
confidence: 99%